Religion and new media : a study on Facebook and Christianity. - Tan, Rystine. (2013)
The religious and the spiritual is increasingly defined by new means of communication, and Christian religious authority are increasingly using social media to reach out to their congregants and with the constant sharing of information, they use social media as a tool to help enhance the congregants’ spiritual experiences and build relations with their congregants. However this may lead to other unwarranted consequences too as the boundaries of religion spills over to the public sphere of social media. This research paper aims to explore how religious-social shaping of technology (a) affects spiritual experience; and (b) affects relations between the Pastor and the congregants.